Splenectomy increases the number of circulating hematopoietic stem/progenitor cells in patients with hepatitis C virus‐associated liver cirrhosis. Issue 14 (25th March 2014) - Masuya, Masahiro; Shiraki, Katsuya; Sugimoto, Kazushi; Yamamoto, Norihiko; Yoneda, Misao; Kanayama, Kazuki; Nishikawa, Kenichiro; Ino, Kazuko; Tawara, Isao; Ohishi, Kohshi; Sakurai, Hiroyuki; Usui, Masanobu; et al.
<x xml:space="preserve">Abstract</x> Aim The spleen is not believed to contribute to hematopoiesis in healthy adults. However, several reports have demonstrated that the spleen in adults contains a large number of hematopoietic stem/progenitor cells (HSC). Although splenectomy increases platelet and leukocyte counts, the effects of splenectomy on circulating HSC have not been elucidated. In this study, we evaluated the association between the number of circulating HSC and splenectomy in patients with hepatitis C virus (HCV)‐associated liver cirrhosis (LC). Methods In 48 patients with various stages of HCV‐associated chronic liver disease and seven patients with LC who underwent splenectomy, and 10 healthy volunteers, we determined the numbers of circulating CD34+ cells and colony‐forming unit culture by flow cytometry and methylcellulose culture, respectively. Plasma stromal cell‐derived factor‐1α (SDF‐1α) concentrations were measured using an enzyme‐linked immunosorbent assay. Results The numbers of circulating CD34+ cells and colony‐forming unit culture decreased but the plasma SDF‐1α concentration increased with the progression of liver disease. There was an inverse correlation between the number of circulating HSC and the plasma SDF‐1α concentration. The numbers of circulating HSC and platelets were determined before and after splenectomy in seven patients with LC. In these patients, the numbers of circulating HSC and platelets increased significantly after splenectomy and the enhancing effect persisted for a long time. Conclusion Our data suggest that the spleen plays an important role in modulating HSC dynamics in patients with HCV‐associated chronic liver disease. Our results also imply that splenectomy may improve liver function in patients with LC.